A Study of Leadership Behaviour of Secondary School Principals of Bareilly - Pandey, Jyoti (JOURNAL OF INDIAN EDUCATION, 2021)
Human capital management is a challenging task. It requires strategic planning and purposeful practices to secure outstanding talent, and apply it as per the goals in the organisational settings (Burn, 1978; Kumar, 2018). The role of school principal is changing from superheroes towards an orchestra conductor who shares his leadership skills and uses it for school management. Through leadership behaviour, school principals give direction to management system for policy implementation, resource allocation and relationship building. The present study is concerned with leadership behaviour of secondary school principals (N=100) of Bareilly district of Uttar Pradesh, which reveals significant differences in leadership behaviour of school principals with reference to the type of institution, gender and locality. Private school principals revealed higher level of leadership behaviour in comparison to government college principals while with reference to gender, female principals showed higher level of leadership behaviour in comparison to male counterparts. On the other hand, in aspects of locality, very few significant differences were found between urban and rural school principals.